Integrally-formed transition metal oxide catalyst as well as preparation method and application thereof
The nanomanganese dioxide catalyst is generated through the redox reaction of manganese nitrate, potassium permanganate and titanium dioxide, and the additives and adhesives are added for integrated molding, which solves the problems of complex and high cost of catalyst preparation in the prior art, and achieves high Catalysts with activity, low temperature catalytic effect and long life, and simple process and environmentally friendly.
Patent Information
- Application Number
- CN202411351324.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
AI Technical Summary
The existing catalyst manganese dioxide preparation technology has problems such as complex process, high cost, and environmental pollution, which is difficult to meet the needs of industrial production, especially in terms of low-temperature catalytic activity and service life.
By forming nanomanganese nitrate, potassium permanganate and titanium dioxide in the redox reaction, and adding auxiliary materials and binder for integrated molding, a high-active catalyst is formed by high-temperature calcination, and the catalytic performance is improved by using the promoter effect of titanium dioxide. , and the waste gas is absorbed and treated by potassium hydroxide.
A nanomanganese dioxide catalyst with high activity and good low-temperature catalytic effect is achieved, the preparation process is simplified, the production cost is reduced, and the catalyst is environmentally friendly, and the catalyst has a long service life.
Smart Images

Figure CN119236919A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an integrally formed transition metal oxide catalyst and a preparation method and application thereof, belonging to the technical field of volatile organic waste gas treatment. Background Art
[0002] Volatile organic compounds (VOCs) usually refer to organic compounds with a saturated vapor pressure greater than 70Pa at room temperature and a boiling point of less than 260°C at normal pressure. They mainly come from industries such as petrochemicals, medicine, spraying, printing, rubber, shoemaking, and coking, and include hydrocarbons, alcohols, ketones, aldehydes, esters, ethers, aromatic hydrocarbons, and halogenated hydrocarbons. Catalytic combustion technology for treating VOCs is an important method for treating VOCs waste gas. It has been vigorously promoted and popularized in recent years. It can oxidize and decompose combustible substances in waste gas at a lower temperature, and the oxidation products are non-polluting CO2 and H2O.
[0003] Precious metal catalysts have good low-temperature catalytic activity and are currently the most widely used catalysts for low-temperature treatment of VOCs. In particular, catalysts containing precious metals Pt and Pd have received extensive attention and research. However, various problems often arise in practical applications, such as volatilization, sintering and poisoning of active components. In addition, precious metals are expensive, which leads to high cost of using precious metal catalysts, which restricts the development of precious metal catalysts and limits their commercial application. Therefore, it is necessary to seek alternative materials to reduce catalyst costs.
[0004] Transition metal oxides such as manganese oxide, copper oxide, zirconium oxide, cobalt oxide, nickel oxide, etc. are all active catalytic combustion catalysts. At the same time, due to the wide source of transition metals, low cost, simple preparation method and good catalytic effect, they have more potential for industrial application. In particular, nano manganese dioxide, as an environmentally friendly catalyst, has been widely studied and applied.
[0005] There are many methods for preparing nano manganese dioxide, such as hydrothermal method, sol-gel method, coprecipitation method, solid phase synthesis method, etc. The hydrothermal method generally uses KMnO4 and MnSO4 as raw materials, and reacts to prepare manganese dioxide at a certain temperature and pressure, or uses KMnO4 alone as raw material and prepares it through its disproportionation reaction. The sol-gel method mainly uses manganese acetate and citric acid as raw materials for preparing manganese dioxide, and goes through sol, gel, drying, heat treatment and other steps. In order to control the composition, structure, size, morphology, etc. of manganese dioxide when preparing manganese dioxide by coprecipitation, adding template materials can more accurately synthesize nano manganese dioxide with controllable size, shape and structure. The solid phase synthesis method is to mix the solid reactants and pass them through the high-speed spheroidal graphite method, and then prepare nano manganese dioxide by treatment.
[0006] However, these preparation methods also have some shortcomings. For example, the hydrothermal method will produce sulfur-containing wastewater and waste gas when mass-producing catalysts, which is difficult to handle. The sol-gel method takes a long time to prepare. The co-precipitation method is difficult to make the template clear or the process is complicated. The solid-phase method takes a long time to grind to the required size. Summary of the invention
[0007] In view of the defects in the existing technology for preparing manganese dioxide catalysts, the first object of the present invention is to provide a method for preparing an integrally formed transition metal oxide catalyst. The method uses integral forming, has a simple process, is beneficial to industrial production, and the obtained product has high catalytic activity.
[0008] The second object of the present invention is to provide an integrally formed transition metal oxide catalyst, which is integrally formed and whose components except for the adhesive are all composed of active components with catalytic effects. It has the advantages of high catalytic activity, large specific surface area and high temperature resistance.
[0009] The third object of the present invention is to provide an application of an integrally formed transition metal oxide catalyst, which is used to catalyze the oxidative decomposition of volatile organic compounds, and has a longer service life while achieving the same low-temperature catalytic effect as a precious metal catalyst.
[0010] In order to achieve the above technical objectives, the present invention provides a method for preparing an integrally formed transition metal oxide catalyst, which comprises mixing a solution containing manganese nitrate, titanium dioxide and potassium permanganate to perform an oxidation-reduction reaction, adding auxiliary materials and a binder to obtain the product, and then performing molding and high-temperature calcination to obtain the product.
[0011] The mechanism of the technical solution of the present invention is that potassium permanganate and manganese nitrate solution react under the promotion of titanium dioxide to generate manganese dioxide, and the manganese dioxide generated by the reaction is nanometer-level and has high catalytic activity; and in this process, after the reaction is completed, the titanium dioxide is 4+ It can be doped into the manganese dioxide crystal structure as a co-catalyst component, changing the manganese dioxide crystal structure and increasing the Mn available for adsorption of organic molecules. 4+ The catalyst has better formability and processability by adding auxiliary materials and adhesives, and finally, the excess water is removed by high-temperature calcination, and the excess manganese nitrate is decomposed. The high-temperature reaction of the adhesive allows the main components of manganese dioxide, titanium dioxide and auxiliary materials to be tightly connected, and the product has a higher specific surface area, which fully ensures that the volatile organic matter can fully contact the catalyst surface when passing through the catalyst, thereby achieving high low-temperature catalytic activity.
[0012] In addition, the advantage of using manganese nitrate and potassium permanganate to react and generate manganese dioxide in the present invention is that excess manganese nitrate can be decomposed synchronously to form manganese dioxide and nitrogen dioxide during high-temperature roasting, further increasing the content of manganese dioxide with main catalytic activity in the catalyst, while nitrogen dioxide can be absorbed by potassium hydroxide solution, achieving environmental friendliness. And the inventors found that if the manganese nitrate used in the present invention is not excessive relative to potassium permanganate, the subsequent solids also contain potassium permanganate, and potassium manganate will be present during high-temperature roasting, which cannot be completely converted into manganese dioxide, resulting in reduced activity of the catalyst.
[0013] As a preferred solution, the auxiliary material is at least one of magnesium oxide, silicon oxide, aluminum oxide and molecular sieve. The auxiliary material used in the present invention can not only serve as a catalyst promoter to synergistically improve the catalytic performance of the catalyst, but also play a role as a skeleton during molding.
[0014] As a preferred solution, the binder is at least one of methyl cellulose, carboxymethyl cellulose, carboxymethyl propyl cellulose, hydroxypropyl methyl cellulose and starch.
[0015] As a preferred solution, the conditions for the redox reaction are: temperature of 80-100° C. and time of 4-30 h.
[0016] As a preferred solution, the molding is extrusion molding or compression molding. The catalyst can be molded into spherical, columnar, granular, honeycomb, ring, square or irregular shapes.
[0017] As a preferred solution, the conditions of high temperature calcination are: temperature of 200-400°C and time of 2-5h. The present invention can dry the catalyst by high temperature calcination while decomposing excess manganese nitrate into manganese dioxide. However, nano manganese dioxide is prone to deoxidation at too high a temperature, and becomes low-valent manganese ions such as Mn2O3 or Mn3O4, which will lead to reduced catalyst activity or complete inactivation; at the same time, if the calcination time is too short or the calcination temperature is too low, manganese nitrate cannot be completely decomposed, and if the calcination time is too long, energy will be wasted and the catalytic activity will not be further improved.
[0018] As a preferred solution, the raw materials include, by weight: 80-100 parts of potassium permanganate, 135-170 parts of manganese nitrate, 0.1-1 part of titanium dioxide, 0.1-1 part of auxiliary materials, and 0.1-1 part of adhesive. The amount of each raw material used in the present invention is very critical. The amount of potassium permanganate directly affects the amount and quality of manganese dioxide produced, and is the key to determining the activity of the catalyst. Too high or too low an amount will affect the balance of the redox reaction, and then affect the formation of the crystalline structure of manganese dioxide, and have a direct impact on the generation of active sites and low-temperature catalytic performance of the catalyst; the amount of manganese nitrate needs to be excessive relative to potassium permanganate, while ensuring that potassium permanganate is completely decomposed into manganese dioxide. At the same time, excess manganese nitrate can be synchronously decomposed during high-temperature roasting to form manganese dioxide and nitrogen dioxide, further increasing the content of the main catalytically active manganese dioxide in the catalyst. Titanium dioxide acts as a co-catalyst in the reaction, promoting the redox reaction while Ti 4+ Doping into manganese dioxide crystals changes its structure and increases Mn 4+ Active sites and oxygen vacancies, thereby helping to improve the catalytic performance of the catalyst, further preferably titanium dioxide is 0.1-0.2 parts, and manganese nitrate is 140-150 parts. The amount of binder needs to be controlled together with the amount of auxiliary materials to ensure that the catalyst has a certain pore structure and that the components have a certain formability to ensure the durability of the catalyst during use.
[0019] As a preferred solution, potassium hydroxide solution is used to absorb tail gas during high temperature roasting. The present invention uses potassium hydroxide solution mainly to absorb nitrogen dioxide gas generated by decomposition of excess manganese nitrate.
[0020] The present invention provides a method for preparing an integrally formed transition metal oxide catalyst, which specifically comprises the following steps:
[0021] (1) first add water to a container, then add manganese nitrate and titanium dioxide, stir evenly, then slowly add potassium permanganate, heat to 80-100° C. under stirring, and keep for 4-30 hours, so that potassium permanganate and manganese nitrate react under the action of the promoter titanium dioxide to generate active ingredient manganese dioxide, and filter after the reaction is completed;
[0022] (2) adding auxiliary materials to the solid obtained in step 1;
[0023] (3) adding a binder to the solid obtained in step 1, mixing evenly, and repeatedly kneading or mixing until there are no lumps or bubbles;
[0024] (4) shaping the product obtained in step 3, which can be formed by extrusion or molding, and the shape can be spherical, cylindrical, granular, honeycomb, ring, square or irregular;
[0025] (5) Place the product after molding in step 4 in a high temperature furnace, raise the temperature to 200-400°C, and maintain it for 2-5 hours, while drying the product, decomposing the excess manganese nitrate into manganese dioxide. Take it out and cool it to room temperature to obtain the catalyst;
[0026] (6) absorbing the NO2 produced by the high-temperature decomposition in step 5 with a potassium hydroxide solution;
[0027] (7) Add potassium hydroxide to the solution containing nitric acid and potassium nitrate obtained by filtering in step 1 and stir evenly, and mix the solution in step 6, and carry out concentration treatment through a reverse osmosis membrane. The obtained pure water can be used in step 1, and the residue can be exported as potash fertilizer.
[0028] The present invention also provides an integrally formed transition metal oxide catalyst obtained by the above-mentioned preparation method, which has the advantages of high catalytic activity, large specific surface area and high temperature resistance.
[0029] The present invention also provides an application of an integrally formed transition metal oxide catalyst, which is applied to catalyze the oxidation and decomposition of volatile organic compounds. In the catalyst of the present invention, manganese dioxide accounts for 90% to 98% of the total mass of the catalyst, and the catalytic activity is high.
[0030] As a preferred solution, the volatile organic matter includes at least one of ethyl acetate, butanone, n-butanol, toluene, xylene, trimethylolbenzene, styrene, n-hexane, cyclohexane and diethylenetriamine.
[0031] Compared with the prior art, the technical solution of the present invention brings about innovative and beneficial technical effects:
[0032] 1) The catalyst prepared by the present invention is integrally formed, has high quality, all components are active components, has good low-temperature catalytic effect, and has a simple preparation process, is easy to operate, and is suitable for mass production.
[0033] 2) The raw materials used in the present invention only generate NO2 gas during the preparation process, which is easily absorbed and treated by alkaline solution and is environmentally friendly.
[0034] 3) The wastewater generated in the preparation process of the present invention is mainly potassium nitrate, which can be exported as potash fertilizer after being collected and treated, thereby protecting the environment and reducing costs and increasing efficiency.
[0035] 4) The present invention adds titanium dioxide during the preparation process, which can effectively promote the reaction and reduce the reaction time. 4+ It can be doped into the manganese dioxide crystal structure, change the manganese dioxide crystal structure, and increase the Mn available for adsorption of organic molecules. 4+ and oxygen vacancies, which significantly improved the catalytic performance of the catalyst.
[0036] 5) The nano manganese dioxide catalyst prepared by the present invention can be molded into spherical, cylindrical, granular, honeycomb, ring, square or irregular shapes by adding methyl cellulose, starch, aluminum oxide powder, etc., through a series of processes such as mixing, kneading, molding, and roasting. It is convenient to place it in the fixed bed of the catalytic furnace, with simple operation, mild reaction conditions, low operating cost, and good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The conversion temperatures of the catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 3 for common organic substances at T98.
[0038] Figure 2 The figure is a comparison curve of toluene conversion rate of the catalysts prepared in Example 1 and Comparative Example 1.
[0039] Figure 3 The conversion temperatures of the catalyst prepared in Example 5 to common organic compounds T50 and T98 after being treated at 600°C for 10 hours.
[0040] Figure 4 This is a test chart of the catalytic life of the catalyst prepared in Example 5. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be further described below in conjunction with specific embodiments of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; these embodiments are only for a better understanding of the present invention, rather than limiting the scope of protection of the present invention.
[0042] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.
[0043] Example 1
[0044] Accurately weigh 10.1g of deionized water into a conical flask, weigh 0.2g of titanium dioxide and 148.2g of manganese nitrate into the conical flask, stir evenly, weigh 87.3g of potassium permanganate and slowly add it to the above solution while stirring, place the conical flask in an oil bath, heat to 85°C, heat and stir for 4h, take out and filter, add 0.2g of aluminum oxide powder, 0.1g of methyl cellulose and 0.1g of starch to the obtained solid, mix well, place in a ziplock bag, knead well, take out, shape into a columnar catalyst with a diameter of 3mm and a length of about 5cm, place on a baking tray and place in a high-temperature furnace at 210°C for 4h, take out and cool to room temperature to obtain the catalyst.
[0045] Example 2
[0046] Accurately weigh 10.1g of deionized water into a conical flask, weigh 0.3g of titanium dioxide and 148.2g of manganese nitrate into the conical flask, stir evenly, weigh 87.3g of potassium permanganate and slowly add it to the above solution while stirring, place the conical flask in an oil bath, heat to 85°C, heat and stir for 4h, take out and filter, add 0.2g of aluminum oxide powder, 0.1g of methyl cellulose and 0.1g of starch to the obtained solid, mix thoroughly, place in a ziplock bag, knead thoroughly, take out, shape into a columnar catalyst with a diameter of 3mm and a length of about 5cm, place it on a baking tray and place it in a high-temperature furnace at 210°C for 4h, take it out and cool to room temperature to obtain the catalyst.
[0047] Example 3
[0048] Accurately weigh 10.1g of deionized water into a conical flask, weigh 0.1g of titanium dioxide and 148.2g of manganese nitrate into the conical flask, stir evenly, weigh 87.3g of potassium permanganate and slowly add it to the above solution while stirring, place the conical flask in an oil bath, heat to 85°C, heat and stir for 4h, take out and filter, add 0.2g of aluminum oxide powder, 0.1g of methyl cellulose and 0.1g of starch to the obtained solid, mix thoroughly, place in a ziplock bag, knead thoroughly, take out, shape into a columnar catalyst with a diameter of 3mm and a length of about 5cm, place it on a baking tray and place it in a high-temperature furnace at 210°C for 4h, take it out and cool to room temperature to obtain the catalyst.
[0049] Example 4
[0050] Accurately weigh 10.1g of deionized water into a conical flask, weigh 0.2g of titanium dioxide and 160g of manganese nitrate into the conical flask, stir evenly, weigh 87.3g of potassium permanganate and slowly add it to the above solution while stirring, place the conical flask in an oil bath, heat to 85°C, heat and stir for 4h, take out and filter, add 0.2g of aluminum oxide powder, 0.1g of methyl cellulose and 0.1g of starch to the obtained solid, mix thoroughly, place in a ziplock bag, knead thoroughly, take out, shape into a columnar catalyst with a diameter of 3mm and a length of about 5cm, place it on a baking tray and place it in a high-temperature furnace at 210°C for 4h, take it out and cool to room temperature to obtain the catalyst.
[0051] Example 5
[0052] Accurately weigh 10.1kg of deionized water into the reactor, weigh 0.2kg of titanium dioxide and 148.2kg of manganese nitrate into the reactor, stir evenly, weigh 87.3kg of potassium permanganate and slowly add it to the reactor under stirring, heat to 85°C, heat and stir for 20h, take it out and separate the solid and liquid through a centrifuge, add 0.2kg of aluminum oxide powder, 0.1kg of methyl cellulose, and 0.1kg of starch to the solid, place the above-mentioned materials in a mud trainer, start the mud trainer, turn off the mud trainer after 1h, take out the product, transfer it to the extruder to extrude it into the required shape, place it in a baking tray, put it in a high-temperature furnace, heat the high-temperature furnace to 300°C, keep it warm for 4h, and take it out after the furnace temperature drops to room temperature to obtain the product. Add 0.2kg of potassium hydroxide to the liquid separated by the centrifuge, concentrate it through a reverse osmosis membrane, and the resulting pure water can be reused in a bucket, and the residue can be placed in a container for export as potash fertilizer. The specific surface area of the catalyst obtained by the BET method is 50m 2 / g.
[0053] Comparative Example 1
[0054] The only difference from Example 1 is that titanium dioxide is not added, and the remaining steps and conditions are the same to obtain a catalyst.
[0055] Comparative Example 2
[0056] Accurately weigh 10.1g of deionized water into a conical flask, weigh 0.2g of titanium dioxide and 87.3g of manganese nitrate into the conical flask, stir evenly, weigh 87.3g of potassium permanganate and slowly add it to the above solution while stirring, place the conical flask in an oil bath, heat to 85°C, heat and stir for 4h, take out and filter, add 0.2g of aluminum oxide powder, 0.1g of methyl cellulose and 0.1g of starch to the obtained solid, mix thoroughly, place in a ziplock bag, knead thoroughly, take out, shape into a columnar catalyst with a diameter of 3mm and a length of about 5cm, place it on a baking tray and place it in a high-temperature furnace at 210°C for 4h, take it out and cool to room temperature to obtain the catalyst.
[0057] Comparative Example 3
[0058] Accurately weigh 10.1g of deionized water into a conical flask, weigh 0.2g of titanium dioxide and 148.2g of manganese nitrate into the conical flask, stir evenly, weigh 87.3g of potassium permanganate and slowly add it to the above solution under stirring, place the conical flask in an oil bath, heat to 85°C, heat and stir for 4h, take out and filter, add 0.2g of aluminum oxide powder, 0.1g of methyl cellulose and 0.1g of starch to the obtained solid, mix thoroughly, place in a ziplock bag, knead thoroughly, take out, shape into a columnar catalyst with a diameter of 3mm and a length of about 5cm, place it on a baking tray and place it in a high-temperature furnace at 500°C for 4h, take it out and cool to room temperature to obtain the catalyst.
[0059] The catalytic performance of the catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was tested. The test method was as follows: compressed air was used as a carrier gas, and different organic substances were bubbled and then mixed with another air. After being mixed evenly in a mixing bottle, they entered the reactor. The test air velocity was 15000 h -1 , catalyst dosage 10g, gas concentration 1000ppm; use FID detector to detect the inlet and outlet organic gas concentration, use thermocouple thermometer to detect temperature. Test the temperature at which common organic substances (ethyl acetate, butanone, n-butanol, toluene, xylene, trimethylbenzene, styrene, n-hexane, cyclohexane, diethylenetriamine) decompose 98% (T98) under the catalytic action of the catalyst. The results are shown in Figure 1 .
[0060] according to Figure 1 The temperature of organic matter decomposition T98 shows that the prepared catalysts can maintain high catalytic effect at a relatively low temperature. After adding titanium dioxide as a promoter, the temperature of the organic reaction can be effectively reduced, and the catalytic efficiency of the catalyst can be significantly improved. In Examples 1 to 3, for most organic matter, as the amount of titanium dioxide increases, the effect of reducing the temperature of the organic reaction first increases and then decreases, and is best at 0.2g; while for n-butanol, the effect of reducing the temperature of the organic reaction increases with the increase in the amount of titanium dioxide; at the same time, compared with Example 4, Example 1 and Comparative Example 2, when the amount of manganese nitrate is too low, the effect of reducing the reaction temperature of the organic matter is not obvious. This is because the content of the main catalytic active manganese dioxide in the catalyst is significantly reduced, and as the amount of manganese nitrate increases, the effect of reducing the temperature of the organic reaction first increases and then decreases, and has the best effect at the amount of Example 1. In addition, when the calcination temperature in Comparative Example 3 is too high, the activity of the catalyst is significantly reduced. This is mainly because nano-manganese dioxide is prone to deoxidation at too high a temperature and becomes low-valent manganese ions such as Mn2O3 or Mn3O4, which will cause the catalyst activity to decrease or completely deactivate.
[0061] according to Figure 3 By performing a performance test on the catalyst prepared in Example 5 after aging at a high temperature of 600°C for 10 hours, it can be found that the catalyst in Example 5 can still maintain a high catalytic effect at a relatively low temperature, which indicates that the catalyst in Example 5 has excellent high temperature resistance and the catalyst will not be affected and deactivated.
[0062] The catalyst prepared in Example 5 was heated at 300°C for 15000 h. -1 The catalyst life test was carried out on a mixed gas of 1000ppm toluene and ethyl acetate at an air velocity of 1000ppm. The test results are shown in Figure 4 ,according to Figure 4It can be seen that when the treatment is continued for 240 hours, the catalyst conversion efficiency can still be maintained above 98%, indicating that the catalyst has an extremely long service life in treating general organic matter at a relatively low temperature.
[0063] The above embodiments are only for better explanation of the principles and practical applications of the present invention, so that those skilled in the relevant technical field can better understand and utilize the present invention, but they are not intended to limit the patent scope of the present invention. All equivalent changes made using the contents of the present invention are within the patent protection scope of the present invention.
Claims
1. A method for preparing an integrally formed transition metal oxide catalyst, characterized in that: A solution containing manganese nitrate, titanium dioxide and potassium permanganate is mixed to carry out redox reaction, and after obtaining the product, auxiliary materials and adhesives are added in sequence, and then the product is molded and calcined at high temperature.
2. The method for preparing an integrally formed transition metal oxide catalyst according to claim 1, characterized in that: The auxiliary material is at least one of magnesium oxide, silicon oxide, aluminum oxide and molecular sieve.
3. The method for preparing an integrally formed transition metal oxide catalyst according to claim 2, characterized in that: The binder is at least one of methyl cellulose, carboxymethyl cellulose, carboxymethyl propyl cellulose, hydroxypropyl methyl cellulose and starch.
4. The method for preparing an integrally formed transition metal oxide catalyst according to any one of claims 1 to 3, characterized in that: The conditions of the redox reaction are: temperature of 80-100° C. and time of 4-30 hours.
5. The method for preparing an integrally formed transition metal oxide catalyst according to claim 4, characterized in that: The shaping is extrusion shaping or compression molding.
6. The method for preparing an integrally formed transition metal oxide catalyst according to claim 5, characterized in that: The conditions for high temperature calcination are: temperature of 200-400° C. and time of 2-5 hours.
7. A method for preparing an integrally formed transition metal oxide catalyst according to claim 5 or 6, characterized in that: The raw materials include, by weight: 80-100 parts of potassium permanganate, 135-170 parts of manganese nitrate, 0.1-1 part of titanium dioxide, 0.1-1 part of auxiliary materials, and 0.1-1 part of adhesive.
8. The method for preparing an integrally formed transition metal oxide catalyst according to claim 1, characterized in that: Potassium hydroxide solution is used to absorb tail gas during the high-temperature calcination.
9. An integrally formed transition metal oxide catalyst, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. The use of an integrally formed transition metal oxide catalyst according to claim 9, characterized in that: Used to catalyze the oxidation and decomposition of volatile organic compounds.
